ASOSIASI FUNGI MIKORIZA (FMA) ARBUSKULA PADA TANAMAN PENGHASIL GAHARU (AQUILARIA MALACCENSIS) - Sarina, .; Burhanuddin, .; Suryantini, Rosa (Universitas Tanjungpura, 2016)
A. malaccensis is a plants at high economic value with aromatic resin contents that the effect of fungi infection. The increase at A. malaccensis growthwith arbuscular mycorhizal fungi. The purpose at this study to get A. malaccensis with AFM assosiation. Purpose of this study to get information of A. malaccensis. This study condueted for 2 months with take a wood sampling and random root for two level of A. malacensis in plant sampling and trees in Sungai Kelambu village, Tebas district, West Kalimantan area. Observation of soil and root samples carried out in laboratory of the Faculty of Forestry Silviculture Tanjungpura University. This method use spora isolation through gradual proces of wet sceening on the ground, colouring the root of genus level calculate the percentage that is infected by AMF. The result of study was found 6 spora types of AMF from a genus glomus and average percentage of root infection was 33% (moderate) 77% (very high) include in infected of clasify 3 and 5 level. Keyword :Aquilariamalaccensis,Arbuscular Mycorrhizal Fungi (AMF), Association